PARENT COMPANY BANKRUPTCY AND CONSEQUNCES FOR INDEPENDENCE SUBSIDIARIES - Rudy Habibie (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2017)
Provisions in the regulations No. 37 of 2004 on Bankruptcy of the Parent Company has not set either specifically or generally. The absence of this rule results in the absence of a request suspension of obligation for payment of debts of the Parent Company have been granted by the Commercial Court. to protect the rights of creditors of the Holding Company is declared bankrupt by not reducingthe independence of subsidiaries that are not directly involved with the bankruptcy Holding Company, also to find out about the extents to which the principle of Actio Paulina in protecting the legal rights of creditors against the interests of holders of the parent company is declared bankrupt